New Perspectives in Theology of Judaism - Spero, Shubert (Academic Studies Press, 2021)
If it can be said that theology is the philosophical examination of a religion by an insider, then the present collection of essays by Shubert Spero offers us the proper formula for a truly authentic work. The author sets out to rigorously yet sensitively investigate some of the basic concepts and principles of classical Judaism. The topics addressed range from the familiar-"Is God Knowable?" and "Justifying Religious Belief"-to the unusual-"Judaism and the Aesthetic," "Does Judaism Have a Theory of Self?" and "Does Messianism Imply Inevitability?" Current issues are not neglected, and are addressed in sections such as "Religious Zionism: What is it?" and "The Ethical Theory of Judaism." While critical and analytic throughout, the author's style is clear and uncluttered and uses arguments to convince rather than to impress. Neither apologetic nor unnecessarily provocative, Shubert Spero provides a fresh approach to the neglected yet vital domain of Jewish theology.